1999
DOI: 10.1002/(sici)1097-458x(199911)37:11<860::aid-mrc559>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Complete assignment of the1H and13C NMR spectra of secoisolariciresinol diglucoside, a mammalian lignan precursor isolated fromLinum usitatissimum

Abstract: A convenient isolation and purification protocol for secoisolariciresinol diglucoside (1), a precursor of the biologically active mammalian lignans enterolactone and enterodiol, from flax seed is reported together with an extensive 1D‐ and 2D‐NMR study (GE‐HSQC, GE‐HMBC and NOESY) leading to its definitive characterization as 2,3‐bis[(4‐hydroxy‐3‐methoxyphenyl)methyl]‐1,4‐butanediyl bis‐[R‐(R*,R*)]‐β‐D‐glucopyranoside. Copyright © 1999 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The following linear gradient of H 2 O (solvent A) and MeOH (solvent B) was applied: 0 min: 25% B, 35 min: 40% B, 37 min: 95% B, 42 min: 95% B, and 44 min: 25% B, followed by a 5 min equilibration step. SDG (5.4 mg, R t 19.1 min) was isolated, and its structure was confirmed by comparing NMR data with those in literature (Chimichi et al, 1999). …”
Section: Methodssupporting
confidence: 63%
“…The following linear gradient of H 2 O (solvent A) and MeOH (solvent B) was applied: 0 min: 25% B, 35 min: 40% B, 37 min: 95% B, 42 min: 95% B, and 44 min: 25% B, followed by a 5 min equilibration step. SDG (5.4 mg, R t 19.1 min) was isolated, and its structure was confirmed by comparing NMR data with those in literature (Chimichi et al, 1999). …”
Section: Methodssupporting
confidence: 63%
“…Its 1 H NMR spectrum was also essentially identical to that of SDG (1), except for methylene group resonances at the C-9 and C-9′ positions, which appeared as two double doublets at δ 3.92 and 3.58 (see Table 1), in contrast to δ 4.09 and 3.47 in SDG (1). 38 Its HMBC spectrum, after analysis of long-range correlations between H-9(a,b)/C-1a and H-1a/C-9, indicated that the glucose moieties were attached at the C-9 and C-9′ positions of secoisolariciresinol (14). Finally, β-D-glucuronidase treatment gave secoisolariciresinol (14), whose HPLC chiral analysis established it to be the (-)-enantiomer (14a) (Figure 4C).…”
Section: Resultsmentioning
confidence: 98%
“…The retention time of SDG was around 19.6 min. The structure was determined by NMR and MS data analyses and by comparison with those in the literature (Chimichi et al ., ). Coniferin (> 99%) was synthesised (Beejmohun et al ., ).…”
Section: Methodsmentioning
confidence: 97%